Suggested Indications for Enucleation of Solid Pseudopapillary Neoplasms in Pediatric Patients - Cho, Yu Jeong; Namgoong, Jung-Man; Kim, Dae Yeon; Kim, Seong Chul; Kwon, Hyun Hee (Frontiers in Pediatrics, 2019)
Background: Solid pseudopapillary neoplasms (SPNs) are rare, low-grade, malignant neoplasms that can occur in pediatric patients. Although complete resection of the tumor is the principle treatment, SPN enucleation (EN) has been reported to be effective in children. This study aimed to examine the feasibility and safety of EN by comparing it with conventional pancreatectomy (CP), and to present the indications for its use in pediatric patients. Methods: We retrospectively reviewed the medical records of 66 patients who underwent surgery for SPN at our institution from October 1992 to April 2018. Surgical methods, postoperative complications, hospital stay, and recurrence were compared. Results: Of the 66 patients, 15 (22.7%) were treated with EN and 51 (77.3%) were treated with CP. The mean duration of EN operation was 262 min (±145 min) and of CP was 345 min (±195 min). There was no statistically significant difference between the two methods (P = 0.13). To objectively compare the mass size between patients, we introduced a tumor size/intraperitoneal width ratio, which also revealed no significant difference between the two surgery groups (P = 0.21). The EN group had one case of recurrence at the resection site. The complications observed were fluid collection, splenic infarctions, hematomas, pancreatic fistulas, portal vein thromboses, and chylous drainage, among which pancreatic fistulas were the most frequent followed by moderate-severe fistulas in the EN group (P < 0.001). The mean postoperative fasting time (EN 17.0 ± 8.7 days vs. CP 5.1 ± 3.3 days, P < 0.001) and mean hospital stay (EN 23.4 ± 10.0 days vs. CP 13.2 ± 6.5 days, P = 0.002) showed statistically significant differences. Conclusion: Compared with CP treatment, EN of SPNs in children has the disadvantages of prolonged fasting times and hospital stays to recover from moderate pancreatic fistulas. However, if appropriate indications are applied, EN can be considered a safe and effective surgical procedure for children.